Problematic Issues Of Forensic Ballistics And Forensic Explosives Science During Pre-Trial Investigation Of Crimes In Peacetime, Wartime And Post-War Perspectives - Yukhno , Oleksandr; Penzieva , Kateryna (Archives of Criminology and Forensic Sciences, 2024)
The article retrospectively examines the basics of forensic ballistics and forensic explosives science, trends and reasons for trafficking in firearms, weapons, ammunition and explosives in the peaceful pre-war period, as well as since the beginning of military operations in the area of Anti-Terrorist Operation and Joint Forces Operation, and in the current martial law period, and identifies trends with a forecast for the post-war perspective. At the same time, the author analyzes the current national criminal and criminal procedure legislation, including its amendments in terms of qualification and peculiarities of investigating these crimes during various periods. This research also considers its application and the ratio of its implementation in law application activities by investigators, inquiring officers, prosecutors at the stages under study, in particular, when comparing peaceful pre-war times and martial law. The study revealed that during martial law, the number of illicit trafficking cases in firearms, ammunition and explosives remains significant due to their large leakage from de-occupied settlements, from the sites of military operations, during the logistics of their delivery and, in some cases, due to the abuse of authority or negligence on the part of certain heads of military units, their financially responsible persons, violation of the accounting procedures and deficiencies in writing off these military assets. In light of the aforementioned and the consequences of illegal airstrikes, missile and artillery attacks on residential areas, educational, entertainment institutions, and other establishments, recreational facilities and civilian infrastructure of Ukrainian settlements and vehicles with civilians, the number of expert forensic ballistics and forensic explosives examination appointments has significantly increased, and therefore the workload of experts conducting these expert examinations has intensified accordingly. This requires the leadership of expert institutions to set some additional tasks in order to increase the number of experts in this category, and to conduct handwriting and forensic accounting examinations, since when keeping these arms records, interested persons fill out the relevant official document forms by hand. The author states that when considering peculiarities of actions by investigators and inquiring officers, one should take into account and comply with the relevant forensic and ballistic methods and methodologies for inspecting the crime scene with a view to a comprehensive and high-quality detection, recording, seizure and evaluation of firearms, ammunition, explosives, their components and remains as well as other objects found by law enforcement agencies after the shelling, which confirm such facts and investigation results, and will be sent to the International Criminal Court or Tribunal. It is emphasized that issues involving preparation for conducting specific types of forensic examinations remain important, including the proper formulation of questions, taking into account martial law and the use of certain military equipment, missiles and shells, which have been understudied in peacetime and require the application of additional specific expertise, and the resolution of challenging issues related to improving the efficiency of interaction between employees of the ministries and agencies concerned. Based on the results of the research, proposals and recommendations have been developed that will enhance the efficiency of pre-trial investigation and expert research in the above-mentioned promising area.